Farmer business schools - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Farmer business schools help enhance farmer capacity to participate in and benefit from agricultural market chains. It builds on the group-based experiential learning mode of farmer field schools, while shifting from a production- to a marketing-oriented curricular framework. Elements of training include such activities as conducting market assessment SWOT (strengths, weaknesses, opportunities, threats) analysis, identifying and launching new products and packaging, analyzing profit margins, and preparing a business plan. Participants meet with market chain stakeholders, such as traders and supermarket industry representatives, during the course of the program. With much more honed business skills, they “graduate” from the farmer business school with a new product (or products), a business plan, and experience implementing their business plan.